Rancang Bangun Sistem Informasi Penjadwalan Produksi Pada PKIS Sekar Tanjung - Santiasa, Ketut De; Wurijanto, Tutut; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: PKIS Sekar Tanjung are services of processing fresh milk into ultra high temperature (UHT) milk. In production, PKIS Sekar Tanjung most perform the services of processing milk UHT to other companies of them as: Lintang Visikusuma, Green Field, Garuda Food, Indolakto, Danone, dan Kalbe Farma. A product produced a total of 32 kind of product. That problem happened to PKIS Sekar Tanjung is often occurs change in schedule production due to a delay in delivery of the materials and full poduct at a warehouse. So as to run businesses, in the field of processing UHT milk, the department of Planning Production Invetory Control (PPIC) need production scheduling. Production schedule arranged based on the request of the customer and adapted to customers who are other to avoid the same schedule. In addition to preparing the production scheduling the schedule delivery of materials is also required so as not to delay in delivery occurs the material. And it takes also schedule retrieval products to avoid product build up occurs at the warehouse.